DEBUNKING TEN MYTHS ABOUT KIDNEY SUPPORTIVE CARE - Dr. Yong Chang Lai; Dr. Thiveya Theivendran; Dr. Sarah So (Australasian Journal of Clinical Nephrology, 2026)
Kidney supportive care (KSC) is a core component of integrated care for people with kidney failure; yet misconceptions about KSC may impede prompt referral and implementation in routine nephrology practice. Although some practitioners may still assume KSC only comprises end-of-life care, KSC can improve quality of life at any stage of chronic kidney disease (CKD), by addressing symptom burden, supporting shared decision-making and advance care planning, and providing psychosocial support without compromising patients' values and treatment goals. It is not limited to only patients who are ‘dying’ and may include patients actively receiving dialysis and kidney transplantation. This article discusses ten common myths about KSC: (1) KSC and conservative kidney management (CKM) are synonymous; (2) KSC is appropriate only in end-of-life care; (3) dialysis increases survival for all patients; (4) choosing conservative kidney management means we do not provide any further medical care; (5) ‘asymptomatic’ patients do not need supportive care; (6) advance care planning is solely the responsibility of KSC; (7) all CKD-associated pruritis is due to elevated phosphate; (8) there are no options for pain management in ESKD; (9) dying from ESKD is always a “gentle death” and (10) nephrologists have little role in managing patients receiving CKM. We hope that by addressing these common misconceptions we can empower all nephrology care providers to incorporate KSC principles into daily practice and encourage early and appropriate referrals to KSC.